Analisis Faktor yang Mempengaruhi Ketimpangan Distribusi Pendapatan di Provinsi Daerah Istimewa Yogyakarta Tahun 2012-2021 - Neva Rodiyatul Sholikah; Niniek Imaningsih (Jurnal Pendidikan Ekonomi (JUPE), 2022)
Based on statistical data and publications published by BPS shows that Special Region of Yogyakarta is the province with the highest Gini Index ratio in Indonesia. The purpose of this study is to examine the effect from economic growth, the human development index and the open unemployment rate to the income distribution inequality in the Special Region of Yogyakarta Province In this case the analytical tool used is through panel data regression analysis where the existing data is taken from BPS or in the form of secondary data in the period 2012-2021 by using fixed effect model (FEM) as the chosen model. In this study was found that simultaneously show that economic growth, human development index and open unemployment rate simultaneously had a significant effect. Partially, the economic growth variable has a positive and insignificant effect on the inequality of income distribution because of the increasingly unequal income distribution pattern. The human development index variable has no significant negative effect on the inequality of income distribution because good labor productivity will be able to reduce the level of inequality. Meanwhile, the open unemployment rate has a positive and significant effect because the absorption of the existing workforce is still not maximal.